A naturalistic study on side effects of selective serotonin reuptake inhibitors in psychiatric out-patient department - Jha, Amit (Journal of Psychiatrists’ Association of Nepal, 2022)
Introduction: >Antidepressants are one of the most commonly prescribed psychotropic drugs. Six SSRIs are approved for various disorders. SSRIs have fewer side effects owing to its selective blocking the serotonin transporter. Nonetheless SSRI has several troublesome side effects, including nausea, diarrhoea, headache, dizziness, sexual side effects, tachycardia, or weight gain. Methodology: This cross-sectional comprised of 200 patients who were divided into two groups. Group 1 had participants who had received SSRI for less than 6 weeks duration and group 2 had patients who had taken SSRI for more than 6 months. Side effects of medications were recorded using UKU side effect rating scale and causality was ascertained using Naranjo adverse drug reaction probability scale. Results: Among the early side effect group consisting of 100 patients, 40% of patients reported at least one side effect. Tension/inner unrest, nausea and vomiting and orgastic dysfunction was the most common side effect reported. 30% of patients in late side effect group had at least one side effect. Orgastic dysfunction, decreased sexual desire and weight gain were the main side effects reported. All the reported side effects were probably associated due to the prescribed SSRI, as inferred from Naranjo causality scoring system. Conclusion: Escitalopram was the most commonly prescribed SSRI among all the SSRIs. Paroxetine and fluvoxamine were the least prescribed SSRIs. Sertraline was found to cause maximum side effects in the early group and fluoxetine caused the most side effects in the late group. Tension/Inner unrest was the most commonly reported side effects followed by sexual side effects.